Avocado oil alleviates non-alcoholic fatty liver disease by improving mitochondrial function, oxidative stress and inflammation in rats fed a high fat–High fructose diet - García-Berumen, Claudia Isabel; Vargas-Vargas, Manuel Alejandro; Ortiz-Avila, Omar; Piña–Zentella, Rosa María; Ramos-Gómez, Minerva; Figueroa–García, María del Consuelo; Mejía-Zepeda, Ricardo; Rodríguez–Orozco, Alain Raimundo; Saavedra–Molina, Alfredo; Cortés-Rojo, Christian (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is characterized by lipid accumulation in hepatocytes, and in advanced stages, by inflammation and fibrosis. Excessive ROS production due to mitochondrial dysfunction contributes to NAFLD development, making the decrease in mitochondrial ROS production an emerging target to alleviate NAFLD. Previously, we have shown that avocado oil, a source of several bioactive compounds with antioxidant effects, decreases oxidative stress by improving the function of the mitochondrial electron transport chain (ETC) and decreasing ROS levels in mitochondria of diabetic and hypertensive rats. Therefore, we tested in this work whether avocado oil alleviates NAFLD by attenuating mitochondrial dysfunction, oxidative stress and inflammation. NAFLD was induced in rats by a high fat – high fructose (HF) diet administered for six (HF6) or twelve (HF12) weeks. Hepatic steatosis and inflammation were detected in both the HF6 and HF12 groups. Hyperglycemia was observed only in the HF12 group. The HF6 and HF12 groups displayed dyslipidemia, impairments in mitochondrial respiration, complex III activity, and electron transfer in cytochromes in the complex III. This led to an increase in the levels of ROS and lipid peroxidation. The substitution of the HF6 diet by standard chow and avocado oil for six weeks (HF6+AVO+D), or supplementation of the HF12 diet with avocado oil (HF12+AVO), alleviated NAFLD, hyperglycemia, dyslipidemia, and counteracted mitochondrial dysfunctions and oxidative stress. The substitution of the HF6 diet by standard chow without avocado oil did not correct many of these abnormalities, confirming that the removal of the HF diet is not enough to counteract NAFLD and mitochondrial dysfunction. In summary, avocado oil alleviates NAFLD by improving mitochondrial function, oxidative stress, and inflammation.